Strategy of balance control during piruetté in classical ballet - Imura, A.; Kojima, T. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
The purpose of this study was to investigate how ballet dancers control their balance on one leg during pirouetté in classical ballet. The hypothesis was that the classical ballet dancer balances letting the COP locate under the centre of mass (COM) of the whole body by translating the supporting leg. Piruettés by four Russian and one Japanese male ballet dancers were captured. COM, COP and supporting foot kinematics were analysed. The dancers` COPs move after the COMs during the first half of one revolution. Then the COP began to stop near the COM and dancers` body axes became more straight during latter half of one revolution. Most dancers translate the COP under the COM, controlling the COP locations in the supporting foot.